Effects of Different Solid–Liquid Parameters on Flow Characteristics and Performance Output of Mineral Extraction Pumps: Analysis and Experimental Validation - Hong, Shunjun; Li, Yuanwen; Hu, Xiaozhou; Yang, Zihai; Lei, Shaowei; Wei, Pengyun; Hu, Junhong; Wang, Xingpeng (Journal of marine science and engineering, 2025)
It is essential to investigate the performance output and flow characteristics within deep-sea mineral extraction pumps using appropriate numerical calculation methods. In this study, by taking a deep-sea mineral extraction pump prototype as the subject, a small-scale mineral extraction pump model was constructed. Computational fluid dynamics methods, incorporating the SSTk-ω turbulence model and the discrete phase model, were utilized to systematically investigate the pressure distribution, velocity field, streamline patterns, and performance characteristics of the mineral extraction pump under three operating conditions—low flow rate, rated flow rate, and high flow rate—while transporting mineral particles of three distinct sizes. The results demonstrated that the larger size of the mineral particles induced greater disturbance to the liquid phase. Under different flow conditions, the correlations between the particle size and both the head drop rate and power drop rate exhibited distinct characteristics. Experiments verified the rationality and precision of the numerical simulation approach. This study provides a methodological reference for analyzing the flow characteristics and performance output of deep-sea mineral extraction pumps.